Comparison of regulation of 3-hydroxy-3-methylglutaryl coenzyme A reductase in hepatoma cells grown in vivo and in vitro. - Beirne, O R (1976)
Unlike the normal liver, numerous transplantable rodent and human hepatomas are unable to alter their rate of sterol synthesis and 3-hydroxy-3-methylglutaryl coenzyme A (HMG-GoA) reductase [mevalonate: NADP+ oxidoreductase (CoA-acylating), EC 1.1.1.34] activity in response to a dietary cholesterol challenge. It has been suggested that this metabolic defect is linked to the process of malignant transformation. Hepatoma 7288C "lacks" feedback regulation of cholesterol synthesis when grown in vivo but expresses this regulatory property when grown in vitro (then called HTC). Therefore, it was used as a model system to answer whether an established hepatoma cell line that modulates its rate of cholesterol synthesis in vitro can express this property when grown in vivo, and whether cells reisolated from the tumor mass have the same regulatory phenotype as before transplantation. Our results show that long-term growth of hepatoma 7288C in tissue culture has not caused a biotransformation that permits feedback regulation of HMG-CoA reductase when the cells are transplanted back into host animals. In addition, HTC cells reisolated from the tumor mass and established in tissue culture continue to have the ability to regulate HMG-CoA reductase activity. Therefore, malignant transformation is not categorically linked to the loss of the cellular components necessary to regulate sterol synthesis and HMG-CoA reductase activity.